2009
DOI: 10.1128/aac.01145-08
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Activity of Antibiotics in a Model of Human THP-1 Macrophages Infected by a Staphylococcus aureus Small-Colony Variant Strain Isolated from a Cystic Fibrosis Patient: Pharmacodynamic Evaluation and Comparison with Isogenic Normal-Phenotype and Revertant Strains

Abstract: Small-colony variant (SCV) strains of Staphylococcus aureusshow reduced antibiotic susceptibility and intracellular persistence, potentially explaining therapeutic failures. The activities of oxacillin, fusidic acid, clindamycin, gentamicin, rifampin, vancomycin, linezolid, quinupristin-dalfopristin, daptomycin, tigecycline, moxifloxacin, telavancin, and oritavancin have been examined in THP-1 macrophages infected by a stable thymidine-dependent SCV strain in comparison with normal-phenotype and revertant isog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
99
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(110 citation statements)
references
References 56 publications
10
99
1
Order By: Relevance
“…Maximal efficacies of the two drugs are difficult to compare, since the plateau of activity could not be reached for delafloxacin at the concentrations tested in these experiments. Of interest, the dose-effect relationship best fits a bimodal sigmoid, as previously observed with the lipoglycopeptide oritavancin (32). This was interpreted in the latter case as suggesting a dual mode of action or a dual target for the drug.…”
Section: Discussionmentioning
confidence: 55%
“…Maximal efficacies of the two drugs are difficult to compare, since the plateau of activity could not be reached for delafloxacin at the concentrations tested in these experiments. Of interest, the dose-effect relationship best fits a bimodal sigmoid, as previously observed with the lipoglycopeptide oritavancin (32). This was interpreted in the latter case as suggesting a dual mode of action or a dual target for the drug.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to the increased ability of these variants to form biofilms (Al Laham et al, 2007;Häußler et al, 2003;Mitchell et al, 2010aMitchell et al, , 2010bSingh et al, 2009Singh et al, , 2010von Götz et al, 2004), SCVs are well-known for their ability to infect and persist within non-professional phagocytes (Sendi & Proctor, 2009) and there is a limited choice of antibiotics able to act against intracellular bacteria. Nguyen et al (Nguyen et al, 2009a) reported a considerable decrease in the efficacy of most antibiotics against intracellular SCVs in comparison to that seen against extracellular bacteria, but, most importantly, in comparison to their efficacy against the normal-phenotype bacteria. Nevertheless, the authors noted that four antibiotics (quinupristin-dalfopristin, moxifloxacin, oritavancin and rifampicin) were more effective in killing intracellular SCVs.…”
mentioning
confidence: 99%
“…Against intracellular bacteria infecting THP-1 cells (native monocytes or differentiated in macrophages), oritavancin appears to be the most effective of all the antibacterials tested in this model, reaching a true intracellular bactericidal effect (-3 log 10 decrease in bacterial counts), as demonstrated against intracellular MSSA [68,69], MRSA, VISA (including strains collected from a patient with bacteremia) [70], or even small colony variants [71][72][73]. It also proved synergistic with other bactericidal antibacterials such as fluoroquinolones or rifampicin against small colony variants [74].…”
Section: In Vitro Models Of Persistent Infectionsmentioning
confidence: 78%